Sinonasal diffuse large B-cell lymphoma: own clinical observation and literature review - M. A. Mingalimov; E. A. Baryakh; O. L. Kochneva; E. N. Misyurina; Yu. Yu. Polyakov; E. I. Zhelnova; K. V. Yatskov; A. B. Makeshova; T. N. Tolstykh; T. S. Chudnova; D. D. Ivanova; D. V. Lebedev; et al. (Онкогематология)
Diffuse large B-cell lymphoma is the most common immunomorphological variant of lymphoma in adults. Extranodal lesions are observed in a third of patients at the disease onset. The organs most often involved are the gastrointestinal tract, testicles, bones, thyroid gland, and skin. Primary involvement of the nasal cavity and paranasal sinuses occur extremely rarely and cause diagnostic and therapeutic difficulties.The article demonstrates a rare clinical case of newly diagnosed diffuse large B-cell lymphoma with sinonasal tract involvement. It took 6 months to verify the final diagnosis. At the moment, the induction stage of treatment for diffuse large B-cell lymphoma continues, the achieved complete metabolic response is maintained.